PENGARUH E-SERVICE QUALITY DAN E-SATISFACTION TERHADAP REPURCHASE INTENTION - Shinta Shinta; Onsardi Onsardi (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
Repurchase Intention refers to consumers’ behavioral tendency to make repeat purchases after gaining prior shopping experience. In the context of e-commerce, Repurchase Intention is influenced by perceived electronic service quality (E-Service Quality) and electronic customer satisfaction (E-Satisfaction). TikTok Shop, as a social commerce–based e-commerce platform, is required to deliver high-quality services and create user satisfaction in order to maintain consumers’ repurchase interest. This study aims to examine the effect of E-Service Quality and E-Satisfaction on Repurchase Intention among student users of TikTok Shop at the Faculty of Economics and Business, Universitas Muhammadiyah Bengkulu. This research is a quantitative study with a descriptive approach. The population of this study consisted of 328 undergraduate students (cohort 2022) of the Faculty of Economics and Business, Universitas Muhammadiyah Bengkulu, who use TikTok Shop. The sampling technique used was a census, in which all 328 students were included as the sample. Data were collected through questionnaires, and data analysis was conducted using multiple linear regression analysis, accompanied by classical assumption tests, partial tests (t-test), and simultaneous tests (F-test). The results show that E-Service Quality and E-Satisfaction have a positive and significant effect on Repurchase Intention. Partially, E-Service Quality has a significant effect on Repurchase Intention, and E-Satisfaction also shows a significant effect on Repurchase Intention. Simultaneously, E-Service Quality and E-Satisfaction significantly influence Repurchase Intention among student users of TikTok Shop at the Faculty of Economics and Business, Universitas Muhammadiyah Bengkulu. Based on these findings, it can be concluded that E-Service Quality and E-Satisfaction, both partially and simultaneously, have a positive and significant effect on Repurchase Intention among student users of TikTok Shop at the Faculty of Economics and Business, Universitas Muhammadiyah Bengkulu.. Keywords: E-Service Quality, E-Satisfaction, Repurchase Intention, TikTok Shop